Penggunaan LKPD Berbasis PBL dalam Pembelajaran Daring untuk Meningkatkan Hasil Belajar Fisika - Syifa, Naila Hilmiyana; Wiyanto, Wiyanto; Astuti, Budi (UPEJ Unnes Physics Education Journal, 2021)
Online learning due to the Covid-19 pandemic that lasted more than a year made students' interest in learning and learning outcomes decrease. Therefore, online learning innovation is needed, one of which is the use of problem-based worksheets. This study aims to describe learning innovations with problem-based worksheets on the Doppler Effect material and to determine the increase in learning outcomes and acceptability responses to students after using problem-based worksheets in online learning. This study uses a pre-experimental method with one group pretest and posttest design. The sampling technique used is purposive sampling. Learning outcomes data were revealed by tests while student responses were revealed through interviews. Tests are given at the beginning and end of learning. Learning outcomes data that have been collected were analyzed quantitatively descriptively. The increase in learning outcomes is seen from the difference between the pretest and posttest scores. Student responses to problem-based worksheets are seen from positive or negative tendencies. The results of this study an increase in learning outcomes and positive responses.